The photon's magnetic field - Evans, Myron W (World Scientific, 1992)
Includes bibliographical references; This book is a collection of papers on a fundamentally new concept in physics — the photon's magnetic field, Bπ. It discusses various applications of Bπ to predict the existence of new magneto-optic phenomena and to reinterpret some of the fundamentals of optics in terms of Bπ of the photon. One of these new phenomena, optical NMR spectroscopy, has already been verified experimentally, leading to a new analytical technique of widespread potential utility.